Case report: Familial case with autism spectrum and bipolar disorder showing a 20q11.21 microduplication including TM9SF4 - Simoncini, Marly; Violi, Miriam; Valetto, Angelo; Bertini, Veronica; Cruz-Sanabria, Francy; Massoni, Leonardo; Dell’Osso, Liliana; Carmassi, Claudia (Frontiers in Psychiatry, 2023)
Autism Spectrum Disorder (ASD) is characterized by multifactorial etiology and high heritability but can be challenging to be diagnosed, especially in cases presenting subthreshold symptoms with no cognitive or language impairment, that may not be identified until adulthood but may occur in family members of subjects with ASD. This study explores the possible correlation between a genomic imbalance and clinical phenotypes in a family case of a proband with ASD, with subjects presenting full-blown or subthreshold ASD and/or mood disorders. Clinical assessments were carried out by means of the: Structured Clinical Interview for DMS-5 Disorders (SCID-5), Autism Spectrum Quotient (AQ), Autism Diagnostic Interview-Revised (ADI-R), Autism Diagnostic Observation Schedule module 2 (ADOS-2) and Adult Autism Subthreshold Spectrum (AdAS Spectrum). Genetic evaluation included Array Comparative Genomic Hybridization (aCGH). The proband was diagnosed with ASD and bipolar disorder BD type I (BD-I), her twin brothers with ASD and intellectual disability (ID), her father and sister with BD type II (BD-II) and autism traits. The proband, her father, twin brothers and older sister showed a microduplication of 350 kb in 20q11.21 while the proband's mother did not present the microduplication or any mental disorder. This study reports a microduplication that segregates with family members affected by ASD or autistic traits comorbid in some cases with bipolar disorder and that has never been reported in healthy subjects. Among the genes harbored in this region, TM9SF4 gene has been recently implicated in risk for ASD.2